Literature review: Perbandingan tingkat nyeri menstruasi (dismenore) sebelum dan sesudah dilakukan hipnoterapi pada remaja putri - Aprilia Mulyani; Evi Zahara; Rahmi Rahmi (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Dysmenorrhea can affect women who experience menstruation at any age. There is no age limit. Almost all women experience discomfort during menstruation, usually accompanied by nausea, dizziness, and even fainting. If it's like this, of course, menstrual pain should not be left alone. This dysmenorrhea can be overcome by pharmacological and non-pharmacological approaches. One of the non-pharmacological approaches that can be used is hypnotherapy.Objective: To determine the comparison of the level of menstrual pain (dysmenorrhea) before and after hypnotherapy in adolescent girls.Method: The method used in this literature review study is to obtain from a search of scientific research articles from the 2015-2020 period using the Google Scholar and Pubmed data bases. A total of 187 articles were obtained and then identification and screening were carried out, so that 10 articles were obtained that matched the inclusion criteria.Results: The average of the articles shows a pValue value <0.005 which means that there is a significant comparison and difference between before being given the intervention and after being given the intervention.Conclusion: There is a comparison of the level of menstrual pain (dysmenorrhea) before and after hypnotherapy in adolescent girls. It is recommended for educational institutions to provide information to all young women about hypnotherapy to reduce menstrual pain (dysmenorrhea).